SOCIO-ECONOMIC STATUS AND FAMILY NUTRITION INFLUENCE ON STUNTING AMONG CHILDREN UNDER FIVE IN THEBELU DISTRICT EAST NUSA TENGGARA PROVINCE - Seran, Sirilius; Sengkoen, Yuliati (Universitas Airlangga, 2024)
Stunting is a condition observed in children under the age of five, characterized by a visibly undernourished physique, often a slender frame with a distended abdomen, or a shorter stature and lighter weight compared to their peers. This malnutrition-induced growth impairment can potentially hinder optimal brain development, thereby compromising cognitive potential. Various factors contribute to stunting in this age group, including demographic, socio-economic, and residential conditions. This research aims to uncover the causal relationship between social and economic status and nutrition variables in relation to the likelihood of stunting. The study focuses on 100 households with children under five in Belu Regency, specifically in Atambua City and Halilulik Village. Employing ordinary least square analysis, the study finds a significant relationship (p=0.002) between residential conditions, education, occupation, and nutrition variables in relation to stunting. This relationship is moderately strong, as indicated by an R-value of 0.427, while the R² value stands at 0.182. Notably, the likelihood of stunting is significantly higher for children whose mothers have an education level of ≤ Junior High School, at 8.081 times, in comparison to those with High School-educated mothers, who are at 8.159 times higher risk, than mothers with a University/Diploma education level. Additionally, children with lower nutritional intake are 4.913 times more likely to experience stunting compared to their well-nourished counterparts, while those from low-income households face a 1.849 times higher risk compared to children from higher-income families.